Mohandas Gandhi : experiments in civil disobedience - Ahmed, Talat (Pluto Press, 2019)
A new critical biography highlighting the contradictions in Gandhi's non-violent philosophy.
Keywords: Gandhi, -- Mahatma, -- 1869-1948.; Gandhi, -- Mahatma, -- 1869-1948; Civil disobedience.; Passive resistance.; Désobéissance civile.; Résistance passive.; HISTORY -- Asia -- India & South Asia.; Civil disobedience; Passive resistance; Gandhi, Mahatma, 1869-1948; Nonviolence; Biography & Autobiography; Political Science; Electronic book.